Outcomes and prognostic factors of infantile acquired hydrocephalus: a single-center experience - Faliang Zhou; Zhao Yang; Zezhong Tang; Yang Zhang; Hongmei Wang; Guoyu Sun; Rui Zhang; Yi Jiang; Congle Zhou; Xinlin Hou; Lili Liu (BMC, 2023)
Abstract Aim To assess the etiologies and adverse outcomes of infantile acquired hydrocephalus and predict prognosis. Methods A total of 129 infants diagnosed with acquired hydrocephalus were recruited from 2008 to 2021. Adverse outcomes included death and significant neurodevelopmental impairment which was defined as Bayley Scales of Infant and Toddler Development III score < 70, cerebral palsy, visual or hearing impairment, and epilepsy. Chi-squared was used to evaluate the prognostic factors of adverse outcomes. A receiver operating characteristic curve was calculated to determine the cutoff value. Results Of 113 patients with outcome data, 55 patients (48.7%) had adverse outcomes. Late surgical intervention time (13 days) and severe ventricular dilation were associated with adverse outcomes. The combination of surgical intervention time and cranial ultrasonography (cUS) indices was a better predictive marker compared with any of them (surgical intervention time, P = 0.05; cUS indices, P = 0.002). Post-hemorrhage (54/113, 48%), post-meningitis (28/113, 25%), and hydrocephalus arising from both hemorrhage and meningitis (17/113, 15%) accounted for a large proportion of the etiologies in our study. Hydrocephalus occurs secondary to post-hemorrhage and had a favorable outcome compared with other etiologies in both preterm and term groups. A significant difference in adverse outcomes between the inherited error of metabolism as a cause and other etiologies (P = 0.02). Conclusion Late surgical treatment times and severe ventricular dilation can predict adverse outcomes in infants with acquired hydrocephalus. It is crucial to identify the causes of acquired hydrocephalus to predict the adverse outcomes. Research into measures of improving adverse outcomes following infantile acquired hydrocephalus is urgently necessary.